To the possibility of liquid dielectrics use in wakefield method of charged particle acceleration - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I. (Вопросы атомной науки и техники, 2013)
Possibility of use of liquid dielectrics for dielectric loaded structures for wakefield acceleration of the charged particles is investigated. Application of liquid dielectric, at its circulation through structure, allows avoiding charge accumulation in volume of dielectric, heating of dielectric, loss of properties under the influence of ionizing radiation, characteristic for firm dielectrics. At change of temperature of liquid dielectric or mixing of liquid dielectrics with various value of dielectric permeability adjustment of dielectric permeability and working frequency of structure is easily feasible. Досліджується можливість використання рідких діелектриків у сповільнюваних структурах для кільватерного прискорення заряджених часток. Застосування рідкого діелектрика, при його циркуляції через структуру, дозволяє уникнути нагромадження заряду в об'ємі діелектрика, нагрівання діелектрика та втрати властивостей під впливом іонізуючого випромінювання, характерних для твердих діелектриків. При зміні температури рідкого діелектрика або змішуванні рідких діелектриків з різним значенням діелектричної проникності легко здійснити регулювання діелектричної проникності та робочої частоти структури. Исследуется возможность использования жидких диэлектриков в замедляющих структурах для кильватерного ускорения заряженных частиц. Применение жидкого диэлектрика, при его циркуляции через структуру, позволяет избежать накопления заряда в объеме диэлектрика, нагрева диэлектрика, потери свойств под воздействием ионизирующего излучения, характерных для твердых диэлектриков. При изменении температуры жидкого диэлектрика или смешивании жидких диэлектриков с различным значением диэлектрической проницаемости легко осуществима регулировка диэлектрической проницаемости и рабочей частоты структуры.